TITANIUM OXIDE DISPERSED ON NATURAL ZEOLITE (TiO2/ZEOLITE) AND ITS APPLICATION FOR CONGO RED PHOTODEGRADATION - Is Fatimah; Eko Sugiharto; Karna Wijaya; Iqmal Tahir; Kamalia Kamalia (Indonesian Journal of Chemistry, 2006)
The utilization of TiO2 dispersed on natural zeolite (TiO2/Zeolite) for degradation of Congo Red photocatlytically has been performed. The TiO2/Zeolite was prepared by mechanically mixing of 100 g of natural zeolite, which it has been heated at 400oC, with TiO2 powder, the final weight ratio of the mixture was 5% (w/w). The mixture was then calcined at 400oC for 6 hours. The calcined product was characterized using x-ray diffractometry, x-ray fluorescence analysis and gas sorption analysis methods to determine its physicochemical properties changes caused by mixing and calcination. Investigation of Congo Red photodegradation using TiO2/Zeolite was carried out by mixing 25 mL 10-4 M solution of Congo Red with 25 mg of TiO2/Zeolite and irradiating the suspention with UV-light of 350 nm for 10, 20, 30, 40, 50 and 60 minutes, respectively. The characterization results showed that dispertion of TiO2 on zeolite resulted in the increasing of titanium concentration on TiO2/Zeolite. The concentration of Ti on natural zeolite was found to be 0.15%(w/w), meanwhile on TiO2/Zeolite was 2.29% (w/w). From X-ray diffractometry analysis result no information was found that TiO2 was dipersed on natural zeolite. It was caused by overlapping of the reflections of zeolite with reflections of TiO2. On the otherhand, the gas sorption analysis result exhibited that the dispersion of TiO2 on zeolite resulted in the decreasing of total pore volume as well as specific surface area of the natural zeolite. The specific surface areas of natural zeolite and TiO2/Zeolite were 21.98 and 16.74 m2/g, respectively, meanwhile the total pore volumes of natural zeolite and TiO2/Zeolite were 20.10x10-3 and 13.47x10-3 mL/g. The simple kinetic of photodegradation of Congo Red exhibited that the rate of degradation followed a first order kinetic and the reaction rate constant was 0.0017 minute-1.